2017
DOI: 10.1002/ccd.26976
|View full text |Cite
|
Sign up to set email alerts
|

Stent placement in the superficial femoral and proximal popliteal arteries with the innova self‐expanding bare metal stent system

Abstract: In the SuperNOVA study, the Innova Stent System demonstrated an excellent safety profile and acceptable clinical outcomes despite the challenging anatomical characteristics of the lesions. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…For the primary effectiveness assessment, the observed primary patency rate was compared with a 60% performance goal determined by adding 10% (estimated drug effect) to the historical patency rate for long lengths of the bare nitinol stent platform. 11 No hypothesis testing was performed for the primary safety outcome, but the MAE-free rate was expected to be similar to the 95% reported at 12 months for the IMPERIAL randomized study. 8 Categorical variables are reported as counts and percentages and continuous variables are reported as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 98%
“…For the primary effectiveness assessment, the observed primary patency rate was compared with a 60% performance goal determined by adding 10% (estimated drug effect) to the historical patency rate for long lengths of the bare nitinol stent platform. 11 No hypothesis testing was performed for the primary safety outcome, but the MAE-free rate was expected to be similar to the 95% reported at 12 months for the IMPERIAL randomized study. 8 Categorical variables are reported as counts and percentages and continuous variables are reported as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 98%
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In selected bare metal stent trials (Table 5), the antithrombotic regimen is not described or elaborated on. [56][57][58][59] The SuperNova trial reported the percentage of patients on any antiplatelet at various points in follow-up but did not make any distinction between SAPT and DAPT. Covered stent trials (Table 6) used DAPT for 6 to 12 months postintervention but similar to other device trials have not uniformly reported precise antithrombotic regimens at various points of follow-up.…”
Section: Antithrombotic Treatment In Device Trialsmentioning
confidence: 99%
“…For example, the LifeStent RESILIENT study 15 reported an 81.3% 12-month primary patency with a mean 7.1-cm lesion length. Corresponding data in the SUPERA SUPERB study 16 (78.9% and a mean 7.8-cm length) and Innova SuperNOVA study 17 (66.4% in a mean 9.1-cm length) demonstrate well the decreasing primary patency rates that accompany increasing lesion length in the femoropopliteal segment.…”
Section: Discussionmentioning
confidence: 55%